Bromacil degradation by IT-01 strain Penicillium spp. and its application in a laboratory scale biofilter - Campos-Vargas, Emmanuel (2017)
Bromacil is a pesticide that has been found in water sources in Costa Rica and its degradation in aqueous matrix has been studied mainly by photochemical methods. This article exposes the Bromacil degradation by a filamentous fungus identified as strain IT-01 Penicillium spp, isolated from contaminated soil and its application in a laboratory scale biofilter. The tests were made at Applied Environmental Engineering laboratories and the Center for Research and Chemical-Microbiological Services at Costa Rican Institute of Technology. The removal efficiency using the microorganism in an aqueous suspended medium was 50% in 72 hours; however, adhering the fungus and used in a marine sponge in  biofilter it was obtained a removal efficiency of 80% with retention times from 18 to 39 seconds. During the biofilter tests: the type of marine sponge as a supporting mean, the effect of inoculation of the filter medium and the hydraulic retention time were evaluated. Through Minitab software, it was determined at 95% confidence that the inoculation of the medium was the only parameter that significantly affects the efficiency of removal for this pollutant.